2017
DOI: 10.1063/1.4990689
|View full text |Cite
|
Sign up to set email alerts
|

Improved interface properties of GaN-based metal-oxide-semiconductor devices with thin Ga-oxide interlayers

Abstract: The impact of thin Ga-oxide (GaOx) interlayers on the electrical properties of GaN-based metal-oxide-semiconductor (MOS) devices was systematically investigated. Thin thermal oxides formed at around 900 °C were found to be beneficial for improving the electrical properties of insulator/GaN interfaces, despite the fact that thermal oxidation of GaN surfaces at high temperatures proceeds by means of grain growth. Consequently, well-behaved capacitance-voltage characteristics of SiO2/GaOx/n-GaN stacked MOS capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 22 publications
5
55
0
Order By: Relevance
“…We do not understand the origin of this reduction. One possibility is the formation of Al x Ga 1-x N at the interface, because the intensity was reported to be decreased with the increase of Al composition in Al x Ga 1-x N [ 20 ]. The interface at the MOS must be confirmed by cross-sectional TEM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not understand the origin of this reduction. One possibility is the formation of Al x Ga 1-x N at the interface, because the intensity was reported to be decreased with the increase of Al composition in Al x Ga 1-x N [ 20 ]. The interface at the MOS must be confirmed by cross-sectional TEM.…”
Section: Resultsmentioning
confidence: 99%
“…3.2.3 . There is still controversy as to whether the GaO x layer formed at the interface between the oxide and GaN layers effectively reduces interface defects [ 20–22 ]. If unintentional oxidation on GaN surface would influence the generation of interface trap states, use of N 2 O/NO in the process of depositing oxide layer instead of H 2 O is alternative approach, especially for the MOS interface at the p -GaN layer.…”
Section: Resultsmentioning
confidence: 99%
“…The growth and development of high-quality dielectrics is of exceptional importance for their incorporation into next-generation GaN high-electron-mobility transistors (HEMTs) because of their great potential in the radio frequency and power switching applications for both lateral and vertical devices. , The high-quality interface and the high tolerance to the electric stress are the main criteria and underlying challenges to both the material selection and growth. Various materials have been adopted on the (Al)­GaN surface as the passivation and gate dielectric layer to improve the device performance and reliability, such as SiO 2 , SiN x , , AlN, Al 2 O 3 , AlON, , HfO 2 , ZrO 2 , MgGaO, and AlSiO .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, gallium oxide (Ga 2 O 3 ) has drawn increasing attention as a dielectric material owing to its superior dielectric properties such as high dielectric constant (9.9-10.2) [4], high breakdown strength (> 7 MV cm −1 ) [5], and high chemical and thermal stability. Ga 2 O 3 thin-films were successfully obtained on various foreign substrates using various techniques such as sputtering [6], atomic layer deposition [7,8], and oxidation [9,10]. Ga 2 O 3 /GaN MOS structures are of particular interest due to the fact that a few monolayers of native Ga 2 O 3 decorate the GaN surface because of the spontaneous termination of the Ga-atoms with oxygen [11,12], affecting the interface property between the oxide and underlying GaN.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee et al grew a Ga 2 O 3 layer on n-type GaN using a photoelectrochemical method involving a He-Cd laser and estimated interfacestate density (D it ) of 2.53 × 10 11 cm −2 eV −1 [13]. Yamada et al characterized D it of thermal oxidized GaO x on GaN to be 1.7 × 10 11 cm −2 eV −1 [6]. These studies indicated the intrinsically superior nature of the Ga 2 O 3 /GaN interfaces, inspired by thermal oxidized SiO 2 with Si that is commonly adopted in silicon CMOS technology.…”
Section: Introductionmentioning
confidence: 99%